Thermal Behavior of a Historic Building Housing Books Across Past and Future Climate Scenarios - Gianluca Cadelano; Alessandro Bortolin; Antonio della Valle; Giovanni Ferrarini; Paola Cattaneo; Fabio Peron; Giuseppe Emmi (Heritage)
Climate change poses significant challenges for the renovation of historic buildings, requiring a careful balance between preservation and energy efficiency, particularly considering the forecasted rise in temperatures. This study focuses on a medieval building undergoing renovation, examining thermal behaviors based on future climate settings, with particular attention to the rooms housing a book collection. Books require controlled microclimatic conditions that must be ensured for their preservation; hence, the energy use for air conditioning control must be considered during the renovation planning phase. Through on-site monitoring of the thermophysical properties of the building envelope and indoor microclimate, along with energy model software simulations, both historic climate and global warming scenarios were evaluated for their potential impact on thermal behavior and consequently on energy consumption. This study aims at contributing to the long-term sustainability and resilience of historic buildings, as well as proposing best practices for planning interventions involving sensitive cultural heritage materials, considering the effects of climate change in the renovation process. The results show strategies to address the climatic changes through a methodology optimizing renovation interventions. The sizing of air conditioning systems coupled with a less stringent microclimate control mitigates energy requirements, in line with the sustainable management approach.